Fever - DeStefano, Lauren (New York : Simon & Schuster BFYR, 2012)
In a future where genetic engineering has cured humanity of all diseases and defects but has also produced a virus that kills all females by age twenty and all males by the age twenty-five, teenaged Rhine escapes her forced marriage and journeys back to New York to find her twin brother.
HL 760
Keywords: Science fiction; Genetic engineering -- Fiction; Orphans -- Fiction; Youths' writings